Pengaruh Harga Dan Kualitas Produk Terhadap Minat Beli Konsumen Pada PT. Kreasi Lutvi Sejahtera (UKM Keripik Singkong) Di Tanjung Morawa - Bakhtiar Putra Demokrasi Zebua; Ade Rahma Ayu (CIVITAS: Jurnal Studi Manajemen, 2022)
This study aims to determine how the effect of price and product quality on consumer buying interest. many types of similar businesses with the same price, causing many competitors / competitors, low product innovation so that they do not have other types of processed cassava, packaging is still manual and product durability is short so that the chips are easily soft.